Finding the Optimal volume and intensity of Resistance Training Exercise for Type 2 Diabetes: The FORTE Study, a Randomized Trial. (August 2017) - Yang, Pearl; Swardfager, Walter; Fernandes, Daniel; Laredo, Sheila; Tomlinson, George; Oh, Paul I.; Thomas, Scott
Highlights: Varied resistance exercise intensity and volume over 6 months did not affect HbA1c. All groups improved with training in HbA1c, insulin, aerobic capacity, and body composition. Providers can aim to tailor resistance training protocols to individual preferences. Abstract: Aim: To compare different volumes and intensities of resistance training (RT) combined with aerobic training (AT) for improvements in glycemic control and cardiovascular health for persons with type 2 diabetes (T2DM). Methods: Participants with T2DM were stratified by HbA1c and randomized: "usual care" (RT1), which consisted of moderate intensity (50% 1-repetition maximum [1-RM]), low volume RT (initiated half-way through program); higher intensity (75% 1-RM) and higher volume (initiated at program onset) RT (RT2); or moderate intensity but higher volume RT (RT3). RT sets and repetitions were adjusted to maintain similar work and volume between RT2 and RT3. Walking or cycling (60–80% aerobic capacity) was prescribed 5 times/week, and RT was prescribed 2 times/week. An ANCOVA, adjusted for baseline and gender, assessed changes post-6 months in glycemic control (HbA1c- primary outcome), aerobic capacity and anthropometrics. Results: Sixty-two participants (52.3 ± 1.2 years, 48% female) were randomized (RT1, n = 20; RT2, n = 20; RT3, n = 22). Only post-training fasting glucose, without significant HbA1c change, was different between groups (RT1–RT3 = −1.7 mmol/L, p = 0.046). Pre-post differences were found in pooled HbA1c (7.4 ± 0.2% [57 ± 2.2 mmol/mol] vs. 6.7 ± 0.2% [50 ± 2.2 mmol/mol], p < 0.001), aerobic capacity (21.5 ± 0.8 vs. 25.2 ± 0.8 ml/kg/min, p < 0.001), body mass (84.0 ± 2.7 vs. 83.0 ± 2.7 kg, p = 0.022 [DXA]), body mass index (30.8 ± 0.9 vs. 30.3 ± 0.8 kg/m 2, p = 0.02) and body fat (32.3 ± 1.1 vs. 31.3 ± 1.2%, p < 0.001). The trial was discontinued early; no HbA1c advantage was found with either RT2 or RT3 over RT1. Conclusions: Combined AT + RT exercise improved glycemic control, cardiovascular risk factors and body composition after 6 months for participants with T2DM, but differential effects between the prescribed intensities and volumes of RT were not found to effect HbA1c.